Evaluation of hydroxyapatite (HA) from waste eggshell strengthened with ultra high molecular weight polyethylene (UHMWPE) by using injection molding process - Taufek, Thoufeili (2019)
This research presents the capability of the waste eggshell as a part of material improvement for the biomedical purpose. Hydroxyapatite ceramics (HA) has been investigated because of its excellent biocompatibility and tissue bioactivity properties. HA from the waste eggshell has been extracted under the calcination process and Tri-Calcium Phosphate (TCP) has been added to the eggshell solution. For the biomedical purposes, some standard should be met in order to implant certain material inside human body. Therefore, this research followed the standard of stoichiometric which has been set by US Food and Drug Administration (FDA) , due to its similarity with the mineral constituents of human bones and teeth which is Ca/P=1.67. HA was analysed under Energy-Dispersive Analysis X-ray system (EDX) in order to investigate the mineral constituent. The HA then was mixed with UHMWPE inside the brabender plastograph machine to form a feedstock. In order to support the process ability of injection molding, the flow ability of the feedstock during injection molding process should be in pseudoplastic form where the viscosity decreased when the shear rate increased [64]. The Taguchi’s Method has been used as the Design of Experiment (DOE) in order to get suitable parameters for injection molding process when HA/UHMWPE were used as a feedstock. In this study, injection temperature, injection pressure, injection time and holding time have been investigated. It was found that, the result from Taguchi’s Method, the optimized parameter for injection temperature, injection pressure, injection time and holding time were 220˚C, 0.6MPa, 7s and 5s respectively. Mixture of HA/UHMWPE again have been analysed by using EDX test and also obtained the value of stoichiometric Ca/P=1.71. The value of flow behaviour, n for each composition are less than 1. Hence, it showed that it was pseudoplastic.